A construção da argumentação em textos dissertativo-argumentativos no vestibular da UEPG - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This dissertation turns to the essay for college admission exam and encompasses a predominantly qualitative dialogical analysis of a corpus with 60 dissertativeargumentative essays that scored above average in 2019’s winter and summer college admission exams for Ponta Grossa State University (UEPG), whose topics were respectively: “What is the worst consequence of the structural racism in contemporary Brazil?” and “Besides school meal, what other actions our country can implement to secure constitutional right to food?”. The question that guides this study is: how the applicants for UEPG admission exam build the argumentation while elaborating their utterances? The methodological-theoretical framework is supported mainly by Antunes (2005, 2016, 2017); Bakhtin (1993, 1997, 2010, 2016, 2019); Bakhtin/Volochínov (1981); Bernardo (2000); Castro (2014); Koch (1993, 2002, 2003); Marcuschi (2005, 2008); Possenti (1993, 2002); Rodrigues (2001); Rojo (2009, 2015) and others. Those authors make clear that language is dynamic, once it surrounds all human activities according to the person’s sphere of circulation, with different voices that appear by means of utterances and bring along ideological values. Thus, the text is comprehended as being permanently in process and it requires an active responsive attitude in order to validate the communication act. Therefore, this study offers an analysis of the sociocultural voices engaged in the essays, based on the answers given to the topic-questions, on the thesis, on the contextualization used to illustrate the theme and on the arguments to support the thesis. For that matter, the observation of the corpus texts allowed to determine that the authors/writers established a dialogue with other utterances, promoting a sociocultural encounter where they recovered their ideological values, their history, their knowledge, all of which go through language and come out as utterances. Those determinations arise as the authors interact with the base text, the writing exam commands and with utterances from varied areas of activity, which highlights the applicants’ observation about the topics in discussion. Besides, the reading repertoire marked the authors’ subjectivity, revealing works they have read, some of them available in the college’s program content. Those voices were embodied by the utterances and come to light recurrently or singularly in the essays, along with formal knowledge derived from specific subjects present in school curriculum, such as Philosophy, Sociology, History, among others, which demonstrates the presence of acquired knowledge in a string of meanings based in the candidate’s discursive memories. In this regard, the college admission exam is an opportunity to verify the successful of learning in the formation process, considering that the students express in it their formal knowledge, deriving from school environment, as well as informal knowledge, deriving from observation of the world.
Keywords: Autoria; Construção da argumentação no Texto dissertativo-argumentativo; Dialogismo; Enunciados; Redação no vestibular da UEPG; Authorship; Construction of argumentation in dissertative-argumentative text; Dialogism; Utterances; UEPG admission exam essay; CNPQ::LINGUISTICA, LETRAS E ARTES::LINGUISTICA